2010
DOI: 10.1016/j.schres.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors in sensory processing of prosody in schizotypal personality disorder: An fMRI experiment

Abstract: Introduction-Persons diagnosed with schizophrenia demonstrate deficits in prosody recognition. To examine prosody along the schizophrenia spectrum, antipsychotic-naïve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 104 publications
0
17
0
Order By: Relevance
“…Differences in production 94,95 and interpretation 96 of prosody have been reported. These deficits should not be surprising given that thought disorder is a defining feature of schizophrenia and schizotypy.…”
Section: Language Productionmentioning
confidence: 96%
“…Differences in production 94,95 and interpretation 96 of prosody have been reported. These deficits should not be surprising given that thought disorder is a defining feature of schizophrenia and schizotypy.…”
Section: Language Productionmentioning
confidence: 96%
“…A total of 54 studies described in 49 publications (2 included both MRI/fMRI (Dickey et al, 2008(Dickey et al, , 2010 and 3 included both MRI/PET (Hazlett et al, 1999;Haznedar et al, 2004;Shihabuddin et al, 2001)) met inclusion criteria. The studies include a total non-independent sample of 1181 SPD and 21,055 healthy control subjects.…”
Section: Identified Studiesmentioning
confidence: 99%
“…Another study used an attention task and found increased activation in the dorsolateral prefrontal cortex, caudate, putamen and thalamus (Hazlett et al, 2008b). The other two studies employed a listening task and both found aberrant activity patterns within the superior temporal gyrus (Dickey et al, 2008(Dickey et al, , 2010. One study reported increased activation when listening to deviant tones versus standard tones in SPD (Dickey et al, 2008), and the other study found decreased activity across all conditions (Dickey et al, 2010).…”
Section: Functional Neuroimagingmentioning
confidence: 99%
“…SPD subjects have deficits in the processing of simple auditory percepts (tones) and higher-order phoneme matching (Dickey et al 2010, Dickey et al 2008). Although SPD subjects may interpret prosody correctly, in a recent fMRI study they were shown to have “inefficient” activation in the superior temporal gyrus (STG) while hearing sentences with happy, sad, sarcastic, or neutral intonation (Dickey et al 2010). Specifically, for healthy comparison subjects, an increase in the extent of activation in the STG in either the left or right correlated with more prosodic sentences correctly identified.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, for healthy comparison subjects, an increase in the extent of activation in the STG in either the left or right correlated with more prosodic sentences correctly identified. For SPD subjects, there was no such relationship between extent of activation and accuracy (Dickey et al 2010). The STG, superior temporal sulcus, and other brain regions considered important for auditory and prosodic processing, thus may have morphological and functional abnormalities in SPD, particularly on the left(Downhill et al 2001, Dickey et al 2003, Dickey et al 1999, Dickey et al 2010).…”
Section: Introductionmentioning
confidence: 99%